Design of a Passenger Ship Launch Using an Air Bag System - Abdullah, Kharis; Sarena, Sryang T. (Jurnal Teknologi, 2024)
Ship launching is one of the stages of ship production before the ship is handed over to the owner, which marks the beginning of the ship's life. With the development of technology at this time, various launching methods have been developed, one of which is the launching method using an air bag system. Launching using air bags has many advantages compared to conventional launching methods that have been used so far. Pre-launch calculations are performed to avoid risks during the launch. Launching using air bags begins with calculating the weight plan of the ship launch and the preparation of the air bag layout. Using CB/T 3837:1998 Technological Requirements for Ship Upgrading or Launching Relying on Air Bags, Shipbuilding Industry Standard, and ISO 14409:2011 ships and marine technology-ship launching air bags, the number of air bag requirements and layout can be determined to support the ship launching process. The passenger ship, with an length overall of 62.80 metres, is planned to have a launch weight of 1058.881 tons. By using the QG6 high-bearing capacity air bag model with 6 layers of cord fabric with a diametre of one metre and a contact length between the air bag and the ship's body of ten metres, a total of 11 air bags are required in a linear arrangement to support the launch of a passenger ship. The distance between air bags is 2.07 metres to 5.736 metres, the longer the distance between air bags, the greater the load supported by each air bag.